2013
DOI: 10.1111/cup.12183
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse dermal angiomatosis associated with calciphylaxis in a patient with end‐stage renal disease

Abstract: Diffuse dermal angiomatosis (DDA) represents a benign, acquired, reactive proliferation of vessels. DDA is clinically characterized by painful livedoid plaques with central ulceration, and the histopathologic hallmark is diffuse endothelial cell hyperplasia in the dermis. DDA has been rarely reported in association with calciphylaxis, a condition characterized by calcification of arterial walls with accompanying thrombosis and cutaneous necrosis. We present a case of a 72-year-old man with end-stage renal dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The relationship between CP and DDA has been described in four published papers to date, for a total of 16 cases. Prinz Vavricka et al concluded that DDA is a common histopathologic finding in the dermis adjacent to necrotizing ulcers in patients with CP; however, the “extent of DDA did not correlate with the gravity or severity of disease.” McMullen et al examined the specificity of fine calcium deposits in vessel walls for CP and found that DDA was only seen in association with CP and no other causes of vascular calcification, namely, gangrene, amputations, chronic stasis, and thrombotic vasculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between CP and DDA has been described in four published papers to date, for a total of 16 cases. Prinz Vavricka et al concluded that DDA is a common histopathologic finding in the dermis adjacent to necrotizing ulcers in patients with CP; however, the “extent of DDA did not correlate with the gravity or severity of disease.” McMullen et al examined the specificity of fine calcium deposits in vessel walls for CP and found that DDA was only seen in association with CP and no other causes of vascular calcification, namely, gangrene, amputations, chronic stasis, and thrombotic vasculopathy.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Diffuse dermal angiomatosis has been reported in association with calciphylaxis, and the extensive proliferation of endothelial cells between collagen fibers in the dermis can mimic a vascular neoplastic process. 12,13 Subcutaneous pauci-inflammatory thrombogenic vasculopathy has been proposed to be the main pathology 14 while the timing and propensity for development of cutaneous microvascular calcific deposits remain uncertain. 15 Special stains such as von Kossa or Alizarin red can highlight calcium phosphate deposits not seen through routine light microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…DDA has been reported on the forearm secondary to iatrogenic arteriovenous fistulas in chronic hemodialysis patients and in women with nonhealing, ulcerating lesions on the breast [ 3 , 4 ]. In addition, this cutaneous reactive pattern has also been reported in association with a variety of diseases that cause vasculopathy, including calciphylaxis [ 5 , 6 ], monoclonal gammopathy [ 7 , 8 ] and cutis marmorata telangiectatica congenita [ 9 ]. The differential diagnosis of DDA includes vasculopathy, medium to large vessel vasculitis, acroangiodermatitis and benign or malignant vascular tumor.…”
Section: Discussionmentioning
confidence: 93%